‘Total pain’: reverence and reconsideration - Rattner, Maxxine (Frontiers in Sociology, 2023)
Dame Cicely Saunders’ conceptualization of ‘total pain’, or ‘total suffering’, is one of her most significant and lasting contributions to the field of palliative care. It was Saunders’ unique combination of knowledge and experiences as a trained social worker, nurse and physician that influenced her understanding of suffering specific to a life-limiting illness as being multi-dimensional: that suffering may be simultaneously physical, psychological, emotional, social, spiritual and/or existential in nature. ‘Total pain’ remains a highly relevant and significant concept within palliative care and Saunders’ lasting contributions are to be revered. This paper invites us to reconsider one particular aspect of Saunders’ conceptualization: that patients’ ‘mental reactions’ to their anticipated dying/death is a key contributor to their ‘total pain’. Drawing upon Saunders’ works from the late 1950s to the early 2000s, this paper details the socio-historical manifestation of this aspect of ‘total pain’ within Saunders’ writings, including influences from her Christian religion and Viktor Frankl, and its enduring impact on palliative care philosophy, practice, and discourse. Then, drawing upon patient stories rooted in my own clinical experiences over a 10 year period as a hospice social worker, I suggest that this particular feature of Saunders’ ‘total pain’ may, unintentionally, work to pathologize both the patient for whom suffering persists and remains unsolvable, and the palliative care clinician who may struggle to relieve it — and why it therefore stands to be revisited. It is my sincere hope and intention that ongoing reverence for Saunders’ significant contributions can sit alongside respectful reconsideration.